Physics of functional materials - Fredriksson, Hasse; Akerlind, Ulla (New Delhi : John Wiley, 2008)
One of the main aims of material science is to understand materials fundamentally so that new materials with tailored properties can be created. Thus, education in material science needs to involve the field of traditional material physics. This textbook provides an introduction to the physics of functional materials with solved examples in the text and exercises for students at the end of each chapter as well as answers to all the exercises at the end of the book.
Answers to exercises 455-474p.; Index 475-480p.; Reprint 2015.
Keywords: Liquids and melts; Mechanical; Properties of gases